2012
DOI: 10.1089/jpm.2012.0208
|View full text |Cite
|
Sign up to set email alerts
|

Associations among Patient Characteristics, Health-Related Quality of Life, and Spiritual Well-Being among Arab Muslim Cancer Patients

Abstract: The FACIT-Sp distinguishes between domains of HrQoL and patient characteristics. Further study on the unique contribution of the FACIT-Sp's Peace and Meaning subscales to HrQoL is needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 13 publications
1
17
0
1
Order By: Relevance
“…Except for two studies, 11,24 overall SpWB revealed the lowest magnitude of association with the physical dimension of QOL, whereas the association with the emotional or functional dimensions was stronger. Lazenby and colleagues, in their investigations in Jordan with predominantly Muslim patients, identified an inverse association between overall SpWB and both the emotional 22,23 and physical dimensions of QOL. 23 These findings were not replicated in a recent study with 153 subjects diagnosed with cancer in an Iranian Muslim population.…”
Section: Sample and Ethodological Characteristicsmentioning
confidence: 98%
See 3 more Smart Citations
“…Except for two studies, 11,24 overall SpWB revealed the lowest magnitude of association with the physical dimension of QOL, whereas the association with the emotional or functional dimensions was stronger. Lazenby and colleagues, in their investigations in Jordan with predominantly Muslim patients, identified an inverse association between overall SpWB and both the emotional 22,23 and physical dimensions of QOL. 23 These findings were not replicated in a recent study with 153 subjects diagnosed with cancer in an Iranian Muslim population.…”
Section: Sample and Ethodological Characteristicsmentioning
confidence: 98%
“…Lazenby and colleagues, in their investigations in Jordan with predominantly Muslim patients, identified an inverse association between overall SpWB and both the emotional 22,23 and physical dimensions of QOL. 23 These findings were not replicated in a recent study with 153 subjects diagnosed with cancer in an Iranian Muslim population. 25 Between factors of SpWB and QOL.…”
Section: Sample and Ethodological Characteristicsmentioning
confidence: 98%
See 2 more Smart Citations
“…The levels of spiritual well‐being were considered neglected dimension when providing holistic nursing care for patients with chronic illness, although the World Health Organization (WHO) indicated to include spiritual well‐being in addition to physical, mental, and social domains in health services . Moreover, spiritual well‐being was correlated with spiritual beliefs and practices, and it was positively correlated with better social and functional well‐being …”
Section: Introductionmentioning
confidence: 99%